Health care demand elasticities by type of service - Ellis, Randall P.; Martins, Bruno; Zhu, Wenjia (Journal of health economics, 2017)
•We estimate within-year demand elasticities for 26 health care service categories.•We analyze 171 million person-months from 73 large employers from 2008-14.•Overall demand elasticity using backward myopic spot prices is -0.44.•Elasticities vary substantially from -0.02 for prevention to -0.44 for pharmacy.•Demand is less elastic for children, hourly nonunion workers, and sicker people. We estimate within-year price elasticities of demand for detailed health care services using an instrumental variable strategy, in which individual monthly cost shares are instrumented by employer-year-plan-month average cost shares. A specification using backward myopic prices gives more plausible and stable results than using forward myopic prices. Using 171 million person-months spanning 73 employers from 2008 to 2014, we estimate that the overall demand elasticity by backward myopic consumers is −0.44, with higher elasticities of demand for pharmaceuticals (−0.44), specialists visits (−0.32), MRIs (−0.29) and mental health/substance abuse (−0.26), and lower elasticities for prevention visits (−0.02) and emergency rooms (−0.04). Demand response is lower for children, in larger firms, among hourly waged employees, and for sicker people. Overall the method appears promising for estimating elasticities for highly disaggregated services although the approach does not work well on services that are very expensive or persistent.